2009
DOI: 10.1007/s11516-009-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

The urban adaptation and adaptation process of urban migrant children: A qualitative study

Abstract: This article employs qualitative research methods to explore the urban adaptation and adaptation processes of Chinese migrant children. Through twenty-one in-depth interviews with migrant children, the researchers discovered: The participant migrant children showed a fairly high level of adaptation to the city; their process of urban adaptation emerged as three categories: the U-Type, the J-type, and the "flat line" type. Also explored were long-term acquisition of explicit behaviors, implicit notions, adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Our results are consistent with recent research in education that has indicated that social interactions in schools may assist rural–urban migrant children to adapt to their new urban environments (Liu et al, 2009). Our results also support the conjecture made by Nielsen et al (2006) that programmes aimed at facilitating social and spatial integration of urban and rural–urban migrant children with the view to promoting intergroup friendships may provide a promising path forward in terms of reducing prejudice between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with recent research in education that has indicated that social interactions in schools may assist rural–urban migrant children to adapt to their new urban environments (Liu et al, 2009). Our results also support the conjecture made by Nielsen et al (2006) that programmes aimed at facilitating social and spatial integration of urban and rural–urban migrant children with the view to promoting intergroup friendships may provide a promising path forward in terms of reducing prejudice between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Migrant children accompany their parents to urban centers, searching for better educational and future career opportunities. Despite their strong desire to stay and become 'permanent residents' in new cities, the adaptation and acculturation process is often long and stressful (Liu et al 2009). Due to economic and cultural discrepancies between urban and rural regions, migrant children often experience social exclusion and prejudice when adjusting to city life.…”
Section: Acculturationmentioning
confidence: 99%
“…For example, the successful experience of adjusting into the host culture creates pleasant feelings of joy, satisfaction, and gratification. On the contrary, the experience of being excluded and marginalized brings feelings of uncertainty and fear (Liu et al 2009). Further, the process of acculturation plays a central role in various aspects of youth development including academic achievement and educational aspirations (Ali 2008;Carranza et al 2009).…”
Section: Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles deserve special mention because of their relevance to this investigation. Liu et al (2009) use a qualitative grounded-theory method to uncover a multi-step framework for understanding the process of assimilation of rural migrant children into urban environments. Finally, Lan (2014) gives much needed clarity to the characteristics of second generation migrant children.…”
Section: Systematic Review Of Existing Literature On Migrant Childrenmentioning
confidence: 99%